Towards consumable XML databases - Huang, Yiwei. (2010)
With the rapid emergence of XML as the de facto standard for information exchange on the World Wide Web, the need for visual query interfaces that can reduce the burden of query formulation and efficiently querying growing XML data sources is fundamental to the spreading of XML to wider community.